The Last Straw: A Bourdieusian Analysis of Motherhood, Mental Health, and Institutional Violence in Tyler Perry's 2025 Film, Straw - Adedokun, Theophilus (Universitas Djuanda, 2025)
This study examines Tyler Perry's 2025 film Straw through Pierre Bourdieu's sociological theory, focusing on intersections of motherhood, mental health, and societal pressure. Despite increasing scholarly attention to Black women's cinematic representation, a significant gap exists in Bourdieusian analyses of contemporary films that centre mental health dimensions of Black motherhood, particularly in dramatic narratives addressing institutional violence. This study addresses three research questions: (RQ1) How does Straw represent the depletion of economic, social, and symbolic capital for Black single mothers within institutional fields? (RQ2) What narrative and visual strategies does the film employ to dramatize symbolic violence and its psychological consequences? (RQ3) How does Perry's film contribute to evolving cinematic representations of mental health in Black motherhood narratives? The study employs qualitative close textual analysis of key scenes across five thematic categories. Analysis includes scene transcription, visual motif identification (framing, sound, montage), Bourdieusian concept mapping, and literature triangulation. Scene selection criteria prioritized moments depicting capital exchange, institutional power dynamics, and psychological transformation. Drawing on Bourdieu's concepts of capital, habitus, field, and symbolic violence, the analysis reveals how the film dramatizes economic, social, and symbolic capital erosion endured by marginalized mothers. The findings document three distinct patterns such as the cascading institutional failures that transform routine encounters into crises, the weaponization of maternal identity through surveillance systems, and the psychological accumulation of symbolic violence leading to breaking points. This study makes three contributions: it extends Bourdieu's symbolic violence concept to cinematic mental health representation, documents emerging patterns in Black motherhood film narratives post-2020, and offers methodological innovations for integrating sociological theory with film textual analysis. The study argues that Straw exposes cumulative effects of societal neglect and stigmatization of Black motherhood, offering critical perspective on systemic barriers limiting agency and wellbeing.